Non-Darcian Effects on Nanoliquid Flow Past a Stretching Sheet with Temperature Jump Condition and Thermal Radiation - Ontela, Surender; Madhu, Macha (Journal of Applied Nonlinear Dynamics, 2026)
This article explores the influence of non-Darcy porous medium on nanoliquid flow past a stretching plane with thermal radiation and thermal slip on surface. The pedesis and thermophoresis effects have been included into the nanofluid model. The equations governing the momentum and energy are initially cast into dimensionless form using the suitable non-dimensional variables. The resultant system of equations is then solved employing variational Finite Element Method (FEM). The impact of pertinent parameters such as thermal radiation, temperature jump, non-Darcy on the flow, temperature and local skin friction coefficient, local Nusselt number are investigated and presented graphically. The Forchheimer number is found crucial to increase temperature and lower the local heat transfer rate in the boundary layer.